International Ranking of Infant Mortality Rates: Taiwan Compared with European Countries - Fu-Wen Liang; Tsung-Hsueh Lu; Mei-Hwan Wu; Hung-Chi Lue; Tung-Liang Chiang; Ya-Li Huang; Lea-Hua Chen (Elsevier, 2016)
Rankings of infant mortality rates are commonly cited international comparisons to assess the health status of individual countries. We compared the infant mortality rate of Taiwan with those of European countries for 2004 according to two definitions. Methods: First, the countries were ranked on the basis of crude infant, neonatal, and postneonatal mortality rates. The countries were then ranked according to the mortality rates calculated after exclusion of live births with a known birth weight of <1000 g, which is the definition set by the World Health Organization. Results: Taiwan was ranked 11th, 12th, and 15th among 26 high-income countries for crude infant, neonatal, and postneonatal mortality rates, respectively. The ranks were 12th, 16th, and 15th, respectively, for mortality rates, excluding live births with a birth weight of <1000 g. However, in only seven, four, and 10 countries were the mortality rate ratios statistically significantly lower than Taiwan in infant, neonatal, and postneonatal mortality, respectively, according to the second definition. Conclusion: The ranking of Taiwan was similar (11th vs. 12th) according the two definitions. However, after consideration of the confidence interval, only six countries (Sweden, Finland, Czech Republic, Belgium, Austria, and Germany) had infant mortality rates statistically significantly lower than those of Taiwan in 2004.